ANALISIS YURIDIS PENANGGULANGAN TINDAK PIDANA PENIPUAN DI BIDANG PASAR MODAL MELALUI PENDEKATAN SISTEM PERADILAN PIDANA (CRIMINAL JUSTICE SYSTEM) - Aloysius Supriyadi; Bismar Nasution; Sunarmi Sunarmi; Syafruddin Sulung Hasibuan (USU LAW JOURNAL, 2015)
ABSTRACT The category of criminal act in capital market is divided into two types: crime and transgression. Fraud in capital market is a crime. This category is different from the other criminal acts because it has its specific characteristics. It is specifically misleading information, viewed from the activity of capital market which is related to tender and stock exchange, stock companies, and institutions and professions which deal with stock market. Fraud in capital market is done by using information or falsified condition so that it will harm a party without having the effect on the manipulated market. Regulation on fraud on material fact in the activity in the stock exchange can be seen in Article 90 of UUPM (Law on Capital Market). Criminal Justice System is used in proactive manner when there is an indication of violation against law on capital market by verifying and/or investigating, based on the report or complaint from capital marketers. Keywords: Fraud in Capital Market, Criminal Justice System